The International Encyclopedia of Media Effects 2016
DOI: 10.1002/9781118783764.wbieme0085
|View full text |Cite
|
Sign up to set email alerts
|

Mood Management Theory

Abstract: Mood management theory belongs to a larger group of theoretical approaches that address selective exposure to media content. The theory posits that media choice is a function of the current affective state of media users and follows the principle of mood optimization. While the existing empirical evidence provides substantial support for the general notion that selective exposure to media content varies as a function of the situational affective state, research also suggests that media choice does not always f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…This leads to the proposal that TV series watching, at least based on the answers gathered in the current focus group, is definitively on the “savoring” side, and therefore leads us to suggest that binge-watching could centrally be an activity serving to enhance or maintain positive affect. Such a view can be strongly supported by mood management theory, the general assumption of which posits that selective media exposure is driven by mood optimization, with motivation not only to terminate or alleviate a negative affective state, but also to preserve and intensify a positive affect ( Reinecke, 2016 ). To serve these hedonistic goals, individuals intuitively rearrange their environment in a way that maximizes positive affect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the proposal that TV series watching, at least based on the answers gathered in the current focus group, is definitively on the “savoring” side, and therefore leads us to suggest that binge-watching could centrally be an activity serving to enhance or maintain positive affect. Such a view can be strongly supported by mood management theory, the general assumption of which posits that selective media exposure is driven by mood optimization, with motivation not only to terminate or alleviate a negative affective state, but also to preserve and intensify a positive affect ( Reinecke, 2016 ). To serve these hedonistic goals, individuals intuitively rearrange their environment in a way that maximizes positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the data collected from our focus group, which particularly emphasized a set of pleasure preservation strategies (e.g., binge-watching scheduling and program selection) among viewers, falls completely within such conceptualization. Further concepts of mood management theory are also particularly meaningful here, such as telic hedonism (i.e., the acceptance of unpleasant affective states in the interest of subsequent hedonic gratifications or long-term hedonic goals); individuals may be willing to delay immediate hedonic pleasure if they anticipate that this will ultimately lead to even greater hedonic gratification ( Reinecke, 2016 ), which is precisely what viewers admitted to doing when they reported in the focus group that they tend to defer viewing a series until they can obtain the whole season to consume it all at once. Coming back to Yee’s taxonomy, other comparable features with drivers of TV series watching can be discernible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both exposure to hedonically and eudaimonically motivated media use has been linked to well-being benefits. Hedonic media entertainment has primarily associated with increased well-being in the form of increased positive and decreased negative affect (for an overview, see Reinecke, 2017), while eudaimonic entertainment has also been identified as a source of more complex forms of psychological well-being, such as feeling self-transcendent emotions such as elevation, awe, or gratitude (e.g., Oliver et al, 2018;Janicke-Bowles et al, 2019). Finally, the satisfaction of the basic psychological needs for autonomy, competence, and relatedness, both in general and via media use specifically, has been linked to various psychological well-being indicators (e.g., Johnson et al, 2020;Vansteenkiste et al, 2020).…”
Section: Effects On Affect Mental Health and Flourishingmentioning
confidence: 99%
“…Media use is considered a particular attractive option for mood regulation because it is an easily accessible and highly customizable feature of one's environment (Bryant & Zillmann, 1984). Furthermore, research referring to mood management theory has repeatedly demonstrated the strong intervention potential of non-interactive media use and its ability to interrupt ruminations about negative events and stressor (Knobloch-Westerwick & Alter, 2006;Reinecke, 2017;Zillmann, 1988Zillmann, , 1991. In recent work on mood management through new, interactive media, Tamborini (2012, 2013) found that following boredom and stress, playing video games of moderate intervention potential resulted in the highest levels of post-gameplay mood repair (2012) and these games were most often selected by individuals in an effort to regulate their moods (2013).…”
Section: Media-induced Recovery: a Review Of The Extant Literaturementioning
confidence: 99%
“…The notion that media entertainment can be an important tool for self-regulation has a long tradition in entertainment research, dating back to the seminal work by Dolf Zillmann on mood management theory (Zillmann, 1988) and selective exposure (Zillmann & Bryant, 1985). This perspective posits that media users are hedonically-driven to dissipate noxious mood states in order to get into hedonically pleasant states (Knobloch-Westerwick, 2006;Reinecke, 2017) and choose contents, which are "excitationally right" for them (Zillmann, 1991, p. 111).…”
mentioning
confidence: 99%